Boosting Nitrogen Reduction to Ammonia on FeN4 Sites by Atomic Spin Regulation. Issue 20 (2nd September 2021) - Wang, Yajin; Cheng, Wenzheng; Yuan, Pengfei; Yang, Gege; Mu, Shichun; Liang, Jialin; Xia, Huicong; Guo, Kai; Liu, Mengli; Zhao, Shuyan; Qu, Gan; Lu, Bang‐An; et al.
Abstract: Understanding the relationship between the electronic state of active sites and N2 reduction reaction (NRR) performance is essential to explore efficient electrocatalysts. Herein, atomically dispersed Fe and Mo sites are designed and achieved in the form of well‐defined FeN4 and MoN4 coordination in polyphthalocyanine (PPc) organic framework to investigate the influence of the spin state of FeN4 on NRR behavior. The neighboring MoN4 can regulate the spin state of Fe center in FeN4 from high‐spin ( d xy 2 dyz 1 dxz 1 d z 2 1 d x 2 − y 2 1 ) to medium‐spin ( dxy 2 dyz 2 dxz 1 d z 2 1 ), where the empty d orbitals and separate d electron favor the overlap of Fe 3d with the N 2p orbitals, more effectively activating N≡N triple bond. Theoretical modeling suggests that the NRR preferably takes place on FeN4 instead of MoN4, and the transition of Fe spin state significantly lowers the energy barrier of the potential determining step, which is conducive to the first hydrogenation of N2 . As a result, FeMoPPc with medium‐spin FeN4 exhibits 2.0 and 9.0 times higher Faradaic efficiency and 2.0 and 17.2 times higher NH3 yields for NRR than FePPc with high‐spin FeN4 and MoPPc with MoN4, respectively. These new insights may open up opportunities for exploiting efficient NRR electrocatalysts by atomically regulating the spin state of metal centers. Abstract : The atomically dispersed Mo–N moieties induce charge accumulation and spin‐state transition of single atom Fe sites, and the eg orbital occupies one electron, which is more conducive to the Fe 3d orbitals overlap with the N 2p orbitals promoting the N2 reduction reaction performance.